In-situ study on nutrient release fluxes from shallow lake sediments under wind-driven waves - 孙远军 卢士强 林卫青 王道增 樊靖郁 李柱 (Journal of hydrodynamics. Series B, 2016)
An in-situ benthic device to measure nutrient fluxes across the sediment-water interface has been developed and successfully used to study both static and dynamic fluxes of nutrients in Dianshan Lake, China. The result shows that the surface sediments of Dianshan Lake were resuspended under wind-driven waves. DOC entered into overlying water only when sediments were resuspended. The average DOC flux was 105.78 mg/（mEd）, while the static and dynamic POC fluxes were 48.22 mg/（mEd） and 10 273.20 mg/（m2d）, respectively. Ammonia and nitrate had no significant release, and the dynamic flux of TN was 87.11 mg/（m2d）. The release of phosphorus was the most evident, and the dynamic fluxes of SRP and DTP were 20.22 mg/（m2d） and 21.78 mg/（mEd）, 2.2 and 2.0 times higher than the static fluxes, respectively. Dissolved phosphorus was released mainly as SRP, and phosphorus release from the sediments in Dianshan Lake cannot be ignored.